FLAT DAN SLIDING DALAM PROFITABILITAS BANK - Dion Yanuarmawan (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2018)
The purpose of this study Analyze and conclude the calculation of flat and sliding using flase method in bank profitability, Studies at PT. BPR Gunung Ringgit Malang. Data analysis technique using Interview, directly PT. BPR Gunung Ringgit Malang Credit Section. Sampling in this research purposive sampling technique is income statement, customer data of flat and sleding credit, and cash flow statement. Based on the Income Statement in 2015, interest income with flat interest payment system is Rp. 2,918,666,748 whereas effective sliding interest payment system is Rp. 2,743,609,937. based on the Income Statement of 2015, interest income with a flat rate payment system of Rp. 3,780,543,752 while the effective sliding payment system is Rp. 3,540,814,991. the results of the above research from the income statement in 2015 and 2016 shows that PT. BPR Gunung Ringgit Malang greatly benefited from the use of installment payment system flat. Payments with a flat interest calculation system may be considered profitable for the bank, it can be seen in the income statement. Payments with the sliding interest calculation system, the amount of the interest installment will decrease according to the loan balance, except on the type of loan that is repayable at the end of the loan term.